Penguatan Literasi Politik Generasi Muda Sumbawa Barat Menjelang Pemilu 2024: Strengthening the Political Literacy of West Sumbawa's Young Generation Ahead of the 2024 Election - Wahyudi, Johan; Aziz SR, Abdul; Saputra, Rizka Donny Agung; Rirahman, Fiqri; Burhanuddin, Burhanuddin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The role of the young voter generation will be more strategic in the national political scene in the 2024 elections. Therefore, the political literacy of the younger generation must be strengthened. Upon this background, the Community Service Team of the Faculty of Social and Political Science Universitas Brawijaya in collaboration with the Research and Innovation Development (RID) Institute of West Sumbawa carried out efforts to strengthen the political literacy of the younger generation of West Sumbawa through a literacy dialog forum and interactive discussions. This activity specifically aims to strengthen the political insights of the younger generation of West Sumbawa through political literacy dialogues, provide skills to present counter-narratives to false information related to the 2024 elections and post-elections and encourage the rise of small communities among the younger generation who are sensitive and able to use social media properly. By combining the use of literacy dialogue methods and interactive discussions, this community service activity has helped strengthen the political literacy of the younger generation ahead of the 2024 elections through several simple efforts.